On the reactivity of mRNA Cap0: C–H oxidative addition of 7-methylguanosine to Pt0 and base pairing studies. Issue 87 (8th October 2020) - Leitão, Maria Inês P. S.; Gonzalez, Carmen; Francescato, Giulia; Filipiak, Zuzanna; Petronilho, Ana
Abstract : The first N-heterocyclic carbene ligand derived from 7-methylguanosine, mRNA cap0, has been prepared by C–H oxidative addition to a platinum(0) complex. Abstract : 7-Methylguanosine, whose lability to form an ylide/NHC has been known for decades, reacts with [Pt(PPh3 )4 ] via C–H oxidative addition to yield a hydrido–Pt II carbene complex. 1 H NMR studies on Watson–Crick base-pairs showed no significant effect of metallation.